Avaliação genética e fenotípica de características reprodutivas e da produtividade acumulada de fêmeas Nelore nas regiões Norte e Nordeste do Brasil - Azevêdo, Danielle Maria Machado Ribeiro (2003)
The objective of this study was estimate genebc parameters for reproductive traits and accumulated productivity (ACP) in females reared Nellore Breeding Program herds. The reproducbve traits studied were age at first calving (AFC), calving interval (CI), post-partum interval (PPI), number of services per concepbon (NSC) and gestation length (GL). The statisbcal analysis were accomplished through the SAS program (Stabstical Analysis System) and the variance components through Restricted Maximum Likelihood Method using the software MTDFREML, fitbng an animal rnodel. The means obtained were: 45.14 ± 10.83 months; 465.55 = 128.49 days; 165.76 ± 110.29 days; 1.34 ± 0.67 services, 295.03 ± 5.85 days and 96.74 ± 46.70 kg of calves weaned by cow at year, respectively for AFC, cr, PPI, NSC, GL and ACP. The significant effects (P<0.05) were: for AFC, female variety*male and sex of calf; for CI and PPI, female variety*male variety and cow's age class; for GL, sex of calf; for NSC, cow's variety and cow's age class; and for ACP, cow's variety. The heritability coefficient estimates for AFC, CI, PPI, NSC,GL and ACP were, respectively: 0.21 ± 0.05 ; 0.05 ± 0.02; 0.32 ± 0.11; 0.05 ± 0.04; 0.12 ± 0.04 and 0.11 ± 0.06. The repeatability for CI, PPI, NSCand GL were, respectively, 0.05; 0.63; 0.22 e 0.09. It was concluded that AFC and GL are important reproductive traits that should be included in selection programo The CI repeatability estimated suggests that female culling based on first performance of the calving interval isn't accurate and there is a risk of culling animais with good reproductive efficiency. The heritability of ACP indicated the existence of enough genetic variability for inclusion it in the improvement programs, which would result in the more productive females in the herds.